Controllable Caustic Animation Using Vector Fields - Baeza Rojo, Irene; Gross, Markus; Günther, Tobias (Eurographics - Short Papers, 2020)
In movie production, lighting is commonly used to redirect attention or to set the mood in a scene. The detailed editing of complex lighting phenomena, however, is as tedious as it is important, especially with dynamic lights or when light is a relevant story element. In this paper, we propose a new method to create caustic animations, which are controllable through constraints drawn by the user. Our method blends caustics into a specified target image by treating photons as particles that move in a divergence-free fluid, an irrotational vector field or a linear combination of the two. Once described as a flow, additional user constraints are easily added, e.g., to direct the flow, create boundaries or add synthetic turbulence, which offers new ways to redirect and control light. The corresponding vector field is computed by fitting a stream function and a scalar potential per time step, for which constraints are described in a quadratic energy that we minimize as a linear least squares problem. Finally, photons are placed at their new positions back into the scene and are rendered with progressive photon mapping.